ANALISIS NILAI PENDIDIKAN KARAKTER DALAM KITAB WADZA`IF AL-MUTA’ALLIM DAN RELEVANSINYA DENGAN MATERI PENDIDIKAN AGAMA ISLAM - Much. Maftuhul Fahmi; Rahmatullah Rahmatullah (STAI Ma'had Aly Al-Hikam Malang, 2022)
This study attempts to analyze the relevance of the values of the book Wadza`if al-Muta'allim by KH. Zainal Abidin Munawwir with material on Islamic Religious Education in Indonesia based on Permendikbud no. 37 of 2018. This type of research is library research with a descriptive qualitative approach and uses content analysis techniques. The results showed: first, it was found that there were 3 (three) parts of the values of character education in the book of Wadza`if al-Muta'allim, namely: wadza`if al-muta'allim at-tholab era, adab al-muta'allim ma'a ustadzih, and wadza`if al-muta'allim wa a'maluhu waqta talaqqi ad-dirasah. Second, the researcher also found 4 (four) categories of relevance of character education values in the Wadza`if al-Muta'allim Book with Islamic religious education materials at the junior and senior high school levels as stipulated in the Minister of Education and Culture Regulation No. 37 of 2018, covering: Fiqh, Akidah Akhlak, Al-Qur'an Hadith, and Islamic History.